Toward a Greener Energy Sector: Examining the Nexus of Environmental Taxes, Green Innovation, and Carbon Disclosure in Nigeria - Sani, Armayau Alhaji; Ma’aji, Muhammad M.; Pantamee , Abdurrahman; Al-batayneh, Rafat; ALShaye, Elias Abduallah; Al-aBSY, Mujeeb Saif Mohsen; Bala, Ahmed Jinjiri; Bala, Hussaini (International Journal of Energy Economics and Policy, 2025)
This study examined the impact of environmental taxes (EN_TAX) and green innovation, considering a sample of 376 firm-year observations. The energy firms were grouped by sector. The data was analyzed using a Generalized Method of Moments (GMM). The coefficient of regression established that EN_TAX exerts a negative and significant effect on emission disclosures, implying that high environmental and energy taxes discourage companies from full emission disclosure. In contrast, the result of green innovation (GREEN_INN) indicates a significant positive coefficient on emissions disclosure, demonstrating that investment in green technologies and renewable energy reduces carbon emissions and environmental degradation. The findings imply that preference should be given to research and investment in renewable energy technologies to enhance a sustainable environment. Our results provide guiding evidence to regulators and corporate policy makers with a framework to promote sustainable environmental and SDGs on clean energy.